Global trends and disparities in burden of blindness and vision loss caused by non-communicable diseases from 1990 to 2021, and forecasts to 2045: a systematic analysis for the global burden of disease study 2021 - Ye, Lingxia; Huang, Xin; Xu, Yufeng (Frontiers in Medicine, 2025)
BackgroundBlindness and vision loss (BVL) is a major public health concern. Non-communicable diseases (NCDs), including cataract, glaucoma, age-related macular degeneration, diabetic retinopathy and etc., were the leading causes of vision impairment globally.MethodsWe extracted global, regional, national, age-and sex-specific data on the prevalence and years lived with disability (YLDs) of BVL caused by NCDs from the Global Burden of Disease Study 2021 (GBD 2021), and then conducted a secondary comparative analysis based on time, location, age, gender, socioeconomic development index (SDI) and health system level.ResultsFrom 1990 to 2021, the global incidence of BVL caused by NCDs continuously increased. In 2021, 1475648.6 thousand BVL cases caused by NCDs occurred globally, and ASR of YLDs reached 371.1 per 100,000 population. Great disparities were found across different genders, ages, and locations. Higher burdens were noted among females, older adult individuals, regions with lower SDI or less advanced health systems.ConclusionThe burden of BVLs caused by NCDs has increased significantly since 1990 and varies widely across regions. Greater efforts are needed in NCDs control and vision protection, especially in older adult individuals and females, in regions with lower SDI, and in regions with less advanced health systems.